Proposed new interior design of NIVEA Spa and Retail for Diethelm (M) Sdn. Bhd. (DKSH) at Lot G-05, G-06, G-07, G-08, G-09/10, Ground Floor, Tropicana City Mall, Jalan SS 20/27, 47400 Petaling Jaya, Selangor Darul Ehsan, Malaysia / Nurul Nazirah Norzan - Norzan, Nurul Nazirah (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Proposed New Interior Design of NIVEA Spa and Retail for DIETHELM (M) Sdn. Bhd. at Lot G-05, G-06, G-07, G- 08, G09/10, Ground Floor, Tropicana City Mall, Jalan SS 20/27, 47400 Petaling Jaya, Selangor Darul Ehsan. This proposed spa is to attract users, in all stage of age such as women, men and also child to try for themselves the treatment that the NIVEA VISAGE produce, at the same time to promote their product successfully as they offered a refreshment treatment and interiors, that comes from their history of the product. The target market for the users of this spa range product is women, man , and teenager from all age and classes, that are concern about their look and appearances, not forgetting to find those who are interested in trying a different type of spa which is a modern spa based on concept and image that the client choose. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself. Connected to that, the chosen design style for NIVEA Spa and Retail is based on modern design, but still apply the traditional spirit and at the same time would attract the customers with different image that they would only get in NIVEA Spa and Retail only. Before getting design, that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, products of the brand, spaces to be concluded in the proposed area, operation time and information's about other spas that use the same system in management, as the proposed spa.